Major cardiovascular events and subsequent risk of kidney failure with replacement therapy: a CKD Prognosis Consortium study. (24th January 2023) - Mark, Patrick B; Carrero, Juan J; Matsushita, Kunihiro; Sang, Yingying; Ballew, Shoshana H; Grams, Morgan E; Coresh, Josef; Surapaneni, Aditya; Brunskill, Nigel J; Chalmers, John; Chan, Lili; Chang, Alex R; et al.
Abstract: Aims: Chronic kidney disease (CKD) increases risk of cardiovascular disease (CVD). Less is known about how CVD associates with future risk of kidney failure with replacement therapy (KFRT). Methods and results: The study included 25 903 761 individuals from the CKD Prognosis Consortium with known baseline estimated glomerular filtration rate (eGFR) and evaluated the impact of prevalent and incident coronary heart disease (CHD), stroke, heart failure (HF), and atrial fibrillation (AF) events as time-varying exposures on KFRT outcomes. Mean age was 53 (standard deviation 17) years and mean eGFR was 89 mL/min/1.73 m 2, 15% had diabetes and 8.4% had urinary albumin-to-creatinine ratio (ACR) available (median 13 mg/g); 9.5% had prevalent CHD, 3.2% prior stroke, 3.3% HF, and 4.4% prior AF. During follow-up, there were 269 142 CHD, 311 021 stroke, 712 556 HF, and 605 596 AF incident events and 101 044 (0.4%) patients experienced KFRT. Both prevalent and incident CVD were associated with subsequent KFRT with adjusted hazard ratios (HRs) of 3.1 [95% confidence interval (CI): 2.9–3.3], 2.0 (1.9–2.1), 4.5 (4.2–4.9), 2.8 (2.7–3.1) after incident CHD, stroke, HF and AF, respectively. HRs were highest in first 3 months post-CVD incidence declining to baseline after 3 years. Incident HF hospitalizations showed the strongest association with KFRT [HR 46 (95% CI: 43–50) within 3 months] after adjustment for other CVD subtype incidence. Conclusion: Incident CVD events strongly and independently associate with future KFRT risk, most notably after HF, then CHD, stroke, and AF. Optimal strategies for addressing the dramatic risk of KFRT following CVD events are needed. Structured Graphical Abstract: Structured Graphical Abstract Hazard ratios (HRs) [and 95% confidence intervals [CIs]) for the risk of kidney failure with replacement therapy (KFRT) associated to developing heart failure (HF), myocardial infarction (MI), atrial fibrillation (AF) or stroke, across 81 global cohorts and graphically depicted using the Optum Labs Data Warehouse database.